Hubungan antara kualiti audit dan struktur pemilikan dengan penyataan semula penyata kewangan dalam kalangan syarikat-syarikat tersenarai di Malaysia - Elham, Faisol (2020)
This study investigated the patterns and types of restatement of financial statements among the listed companies in Bursa Malaysia for the years 2013 to 2015 and also examined the relationship between audit quality and ownership structures with restatement of financial statements. The population was all listed companies except finance companies. The companies involved with the restatement were identified by using Datastream, and the annual reports were subsequently reviewed to determine the patterns and types of restatement. This research finds that 160 companies have restated their financial statements during the stated period. The findings show that financial restatements highly involved companies in the trade and service sector, followed by companies in the the highest type of restatement. Logistic regression was adopted to analyse the data. The regression analyses show that internal audit quality, Big 4 auditors and institutional ownership are related to the occurrence of the restatement of financial statements. This study further finds that the quality of internal audit can reduce the likelihood of financial restatements. Conversely, Big 4 auditor and institutional ownership have positive and significant relationships with the restatement of financial statements. In addition, the results also indicate that the presence of family ownership moderates the relationship between audit committee expertise and financial restatements. This finding implies that family ownership has an effective oversight role in reducing the occurrence of financial restatements. As a result, the moderating role of family ownership could be a reference for policy-makers in developing policies relating to corporate governance in Malaysia by taking into account the view of interest alignment effect in agency theory among family-owned firms.